Phyto – Chemical, Particle Size And High-Performance Thin Layer Chromatography Analysis Of Siddha Formulation Attathi Chooranam (Atc) - Sasvatha, S.; Anpuchelvi, S. (Global Academic Research Institute Colombo, Sri Lanka, 2024)
Siddha medicine is a valuable medicine that has been in practice since the ancient era. Preliminary standardization steps are essential for the identification of active compounds of genuine drugs and for setting analytical standards. The therapeutic potentials of herbal drugs are attributed to the presence of Phytochemicals. The study was done for documentation of qualitative & quantitative parameters of Phytochemicals, particle size, and High- Performance Thin Layer Chromatography analysis (HPTLC) properties of Siddha formulation ATTATHI CHOORANAM (ATC). Preliminary Phyto-chemical screening of ATC established the presence of chemical constituents like Alkaloids, Flavonoids, Glycosides, and Proteins. Quantitative analysis for Phyto-chemicals in aqueous and ethanol extracts showed, that Glycosides (3.7 ± 0.2 μg / ml), Flavonoids (7 ± 0.3 μg / ml) and Protein (52.5 ± 0.2 μg / ml) were maximum quantifiable in ethanol extraction whereas Alkaloids (2.6 ± 0.1 μg / ml) in aqueous extraction. The average particle size of sample ATC 106.711 μm in diameter and the overall distribution of particle is from 4 μm to 600 μm.
Keywords: Attathi chooranam; Phytochemical particle size; HPTLC analysis